The Structure of Zooplankton Community in Floating Net Cages Around Koto Panjang Hidroelectric Reservoir Kampar Regency Riau Province - Fitri, Annisa Sovia; Sumiarsih, Eni; Adriman, Adriman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThe Koto Panjang Hydroelectric Reservoir has changed environmental conditions because of Floating Net Cages (FNC) activities. This condition change the water quality. Zooplankton was biology parameters to determine the changes water quality because zooplankton community is sensitive to changes in aquatic environmental conditions. This research was aims to understand the structure of the zooplankton community around the floating net cagesKoto Panjang hydroelectric Reservoir Kampar Riau. This research has been conducted in May-July 2019. There were three stations. Sampling were conducted 3 times, once/week. The research of zooplankton samples using the sweep method. The results showed density of zooplankton in the around floating net cages Koto Panjang hydroelectric reservoir ranges 1200-1950 organism/L was mesotrophic. The diversity index (H’) ranges 2,602 – 2,979 was moderate criteria. The uniformity index ranges(E) 0,845 – 0,872 was relatively evenly. The dominance index (C) range 0,120 – 0,175 was low dominance. Water quality is supportive for the life of zooplankton was temperatures, pH, transparancy, dissolved oxygen, carbon dioxide-free, and TSS.Keyword: Zooplankton, water quality, density,diversity index, dominanceindex